MATHEMATICAL MODELING OF FORMING OF THE EUTECTIC SILUMIN - E. I. Marukovich; A. M. Branovitskij; Ju. A. Lebedinskij (Литьë и металлургия)
The numerical model of hardening of continuouslycasted eutectic silumin is worked out. The average speed of enthalpy decreasing in different geometrical zones of casting is calculated on its basis. The experimental samples of the continuously casted eutectic silumin microstructure are received.